A Rapid Projection of Water Carrying Capacity in Areas with Community Based Clean Water Supply System in Semarang City - Mellyana Putri Ayu Wandari; Trida Ridho Fariz (Universitas Negeri Semarang, 2025)
The study of water carrying capacity in community-based clean water supply systems is essential for ensuring the sustainability of water resources. In Bulusan Village, Tembalang District, Semarang City, the community-based system established in 2018 faces challenges due to rapid population growth and high educational activities. Without proper assessment, the system risks failing to meet long-term water needs, potentially exacerbating the clean water crisis. This research highlights the importance of understanding water carrying capacity to design sustainable management strategies, ensuring water availability and quality while maintaining an effective and environmentally friendly system. The study also underscores the role of community-based approaches as an alternative solution in areas with limited public services.